The effect on anxiety level of coronary angiographic result and the perception of pain - Atik, Derya; Atik, Cem; Karatepe, Hilal; Karatepe, Celalettin; Çınar, Sezgi (International Journal of Research in Medical Sciences, 2017)
Background: The problems and complications experienced by the patients who underwent a CAG due to their pain and anxiety can be minimized through a care plan prepared to meet their needs and a coordinated teamwork. In this prospective and descriptive study we aimed at determining the effect of coronary angiography results and perceived pain on anxiety level in patients who undergoing coronary angiography. Methods: The study was carried out with patients who were implemented coronary angiography for the first time at the cardiology clinic of Osmaniye private new life hospital between May 2014 and August 2014. The study data were collected using the State-Trait Anxiety Inventory (STAI), a verbal pain rating scale and a questionnaire that was prepared by the investigators. The descriptive data are given in the form of arithmetic mean Standard Deviation (SD), numbers and percentage distribution. The correlations between the variables were assessed using crosstabs, one-way ANOVA and the Pearson's correlation analysis. The data were evaluated in 95% confidence interval and at a significance level of P <0.05. Results: 35.9% of the patients stated that they felt severe pain. The mean anxiety score was 36.746.81 and those who felt very severe and unbearable pain had higher mean anxiety scores (P <0.01). Those who had three coronary diseases had higher anxiety levels (41.149.30) than those who had an atherosclerotic stenosis and #8805;50% (normal) (35.945.49) (P <0.01). Gender had an influence on pain levels (P <0.01). Conclusion: Coronary angiography results and pain perception were determined to be statistically significant effects on anxiety level. A statistically significant correlation was found between pain and anxiety. In general, pain and anxiety affect each other positively; an increase in one results in an increase in the other.